Native Mud Hut, Trinidad, B.W.I. - (:unkn) unknown (Stephens Ltd., Trinidad, 2010)
Postcard from circa 1920, featuring two young boys wearing loincloths standing outside a hut. They are each carrying a bucket on their head. The carrying of items on the head and the wearing of breechcloths, one-piece garments worn to cover the genitals and buttocks, are customs from earliest times.
Colour: Black and white; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Huts--Trinidad and Tobago; Breechcloths--Trinidad and Tobago; Boys--Trinidad and Tobago; Clothing and dress--Trinidad and Tobago; Manners and customs--Trinidad and Tobago; Thatched roofs--Trinidad and Tobago; Dwellings--Trinidad and Tobago; Housing, Rural--Trinidad and Tobago; Pails--Trinidad and Tobago; Gardens--Trinidad and Tobago; Children--Trinidad and Tobago; Ajoupa